DETEKSI DINI STUNTING PADA SISWA KB/RA MANBAIL FUTUH BEJI KECAMATAN JENU TUBAN - Dian Ayu Ainun Nafies; Lilia faridatul fauziah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Nutritional status at kindergarten nutritional status at this age is influenced by nutritional status as a toddler and will affect nutritional status during adolescence, the age when growth spurts occur. Malnutrition early intervention is important if nutritional problems are found, this can be done if nutritional status screening data is available. The rampant cases of stunting are of concern to the government, where the cause of stunting itself is due to a lack of intake since I was still in the womb, a lack of awareness to have health checks, and a lack of sanitation and clean water. Therefore, it is necessary to improve diet, parenting patterns and good sanitation. This study aims to screen the nutritional status of KBRA Manbail Futuh Beji students, Jenu District, Tuban. A total of 33 KB children and 61 RA children participated in this study. Demographic data and anthropometric data were collected. An overview of nutritional status based on weight/age shows the percentage of children with nutritional status of overweight, at risk of being overweight, and underweight, the results are the same, namely 1 child with a percentage of 3.03%. Nutritional status based on height/age shows the percentage of children with short nutritional status as many as 6 children with a percentage of 18.8%. Nutritional status based on weight/height shows the percentage of children with overweight and obese nutritional status with the same results, namely 1 child with a percentage of 3.03% for each result for overnutrition status of 3 children with a percentage of 9.09%. Nutritional status based on BMI/U shows the percentage of children with obese nutritional status as many as 3 children with a percentage of 4.92% overweight and malnutrition as many as 4 children with a percentage of 6.56% the risk of overweight is 1 child with a percentage of 1.64%.